TODDLERS WITH ELEVATED AUTISM SYMPTOMS SHOW SLOWED HABITUATION TO FACES - Webb, Sara Jane (2010)
We explored social information processing and its relation to social and communicative symptoms in toddlers with Autism Spectrum Disorder (ASD) and their siblings. Toddlers with more severe symptoms of autism showed slower habituation to faces than comparison groups; slower face learning correlated with poorer social skills and lower verbal ability. Unaffected toddlers who were siblings of children with ASD also showed slower habituation to faces compared with toddlers without siblings with ASD. We conclude that slower rates of face learning may be an endophenotype of ASD and is associated with more severe symptoms among affected individuals.